Hydrotalcite aramid diaphragm composite material as well as preparation method and application thereof
In-situ growth of hydrotalcite on aramid membranes addresses the thermal and ion conductivity issues of existing diaphragms, enhancing lithium-ion battery performance through improved thermal stability and ion conductivity without increasing thickness.
Patent Information
- Application Number
- CN202411755471.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Existing aramid diaphragms in lithium-ion batteries lack sufficient thermal stability and ion conductivity, leading to issues such as increased thickness and reduced performance, necessitating new materials and processes for improved safety and efficiency.
A method involving the in-situ growth of hydrotalcite on aramid membranes using controlled immersion of metal compounds, followed by washing and drying, to create a hydrotalcite-aramid composite material without altering the diaphragm's thickness.
The hydrotalcite-aramid composite material enhances thermal stability, ion conductivity, and electrochemical stability, improving the cycle stability and safety performance of lithium-ion batteries while maintaining the original thickness.
Smart Images

Figure CN119231092A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrotalcite aramid diaphragm composite material and a preparation method and application thereof, belonging to the technical field of battery diaphragms. Background Art
[0002] With the development of the new energy vehicle market, the technical development of batteries is becoming more and more important, because the performance of batteries will directly affect the development of new energy vehicles. The diaphragm is an important component of lithium-ion batteries. The thermal stability, flame retardancy and ion conductivity of the diaphragm will directly affect the application effect and service life of the battery. Therefore, the development of diaphragms with excellent performance is of great significance to the development of batteries.
[0003] As a new type of heat-resistant diaphragm material, aramid diaphragm can significantly improve the safety performance, rate performance, cycle life and manufacturing efficiency of power batteries due to its excellent heat resistance, insulation, flame retardancy and thermal stability. Chinese patent application CN114479654A discloses a method for preparing an organic intercalated hydrotalcite-aramid coating liquid and its application in lithium battery diaphragm coating. An organic intercalated hydrotalcite is added to the aramid polymerization reaction to obtain an organic intercalated hydrotalcite-aramid coating liquid, which is then coated on a base film, and then washed and dried to obtain a battery diaphragm. However, due to the unique coating process of the aramid diaphragm, the shrinkage performance advantage of the aramid diaphragm at high temperature is not obvious, and it is easy to cause the battery diaphragm to be thicker, which cannot meet the growing demand for batteries. Therefore, new materials and new processes are urgently needed for iterative updates of products. Summary of the invention
[0004] The present invention aims at the deficiencies in the prior art and provides a hydrotalcite aramid diaphragm composite material and a preparation method and application thereof. The diaphragm composite material prepared by the preparation method improves the heat resistance and ion conductivity performance without changing the original thickness of the aramid diaphragm, and the preparation process is simple.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a hydrotalcite-aramid membrane composite material, the preparation method comprising: adding a metal compound for preparing hydrotalcite and an aramid membrane into water, controlling the immersion temperature and immersion time, and after the hydrotalcite is in situ grown on the aramid membrane, washing with clean water and drying to obtain the hydrotalcite-aramid membrane composite material.
[0006] Furthermore, the hydrotalcite is a bimetallic layered hydroxide or a monometallic layered hydroxide; the size of the hydrotalcite is 100-1000 nm.
[0007] Furthermore, the hydrotalcite is at least one of nickel-containing cobalt oxide, nickel-containing aluminum oxide, nickel-containing magnesium oxide, nickel-containing iron oxide, iron-containing nickel oxide, iron-containing cobalt oxide, iron-containing calcium oxide, iron-containing magnesium oxide, iron-containing aluminum oxide, iron-containing sodium oxide, cobalt-containing nickel oxide, cobalt-containing iron oxide, cobalt-containing aluminum oxide, cobalt-containing magnesium oxide, cobalt-containing zirconium oxide, and cobalt-containing sodium oxide.
[0008] Furthermore, the metal compound for preparing the hydrotalcite is selected from at least one of a first metal compound and a second metal compound; The first metal compound is selected from at least one of cobalt-containing oxides, cobalt-containing sulfides, cobalt-containing chlorides, cobalt-containing sulfates, cobalt-containing nitrates, cobalt-containing carbonates, magnesium oxides, magnesium-containing sulfides, magnesium-containing chlorides, magnesium-containing sulfates, magnesium-containing nitrates, and magnesium-containing carbonates; The second metal compound is selected from at least one of nickel-containing oxides, nickel-containing sulfides, nickel-containing chlorides, nickel-containing sulfates, nickel-containing nitrates, nickel-containing carbonates, aluminum-containing oxides, aluminum-containing chlorides, aluminum-containing sulfides, aluminum-containing hydroxides, aluminum-containing sulfates, aluminum-containing nitrates, and aluminum-containing carbonates.
[0009] Furthermore, the metal compound used to prepare the hydrotalcite is a first metal compound and a second metal compound, and the mass ratio of the first metal compound to the second metal compound is 1:(2-6).
[0010] Preferably, the metal compounds are nickel chloride and cobalt chloride.
[0011] Furthermore, for each 30*30cm aramid diaphragm, the added amount of the metal compound is 2-12g; the mass ratio of the metal compound to water is 1:(75-200).
[0012] Furthermore, in the preparation method, alkali is added to the water, and the alkali is at least one of sodium hydroxide or calcium oxide; the mass ratio of the metal compound to the alkali is 1:(0.5-6).
[0013] Furthermore, the soaking temperature is 20-80°C, and the soaking time is 20s-1h.
[0014] A hydrotalcite aramid diaphragm composite material is prepared according to the preparation method of the present invention.
[0015] An application of a hydrotalcite aramid diaphragm composite material, wherein the hydrotalcite aramid diaphragm composite material is applied as a lithium ion battery diaphragm material.
[0016] The beneficial effects of the present invention are: (1) The hydrotalcite aramid membrane composite material of the present invention has a high ionic conductivity (≥0.5 mS / cm 2 ), good temperature resistance (maximum heat shrinkage at 200°C for 1 hour: MD≤10.0%, TD≤9.7%, minimum heat shrinkage: MD≤4.0%, TD≤3.2%), and wide electrochemical stability window. The hydrotalcite prepared by the method of the present invention is anchored on each fiber of the aramid diaphragm at the nano level, which effectively increases the specific surface area of the diaphragm, improves thermal stability and mechanical stability without significantly increasing the thickness of the original aramid diaphragm, and further improves the cycle stability and safety performance of the lithium battery (high temperature hot box, needle puncture, extrusion and heavy object impact) while ensuring the electrical performance of the battery.
[0017] (2) The hydrotalcite aramid diaphragm composite material of the present invention has high ionic conductivity, which can improve the fast charging and rate performance of lithium batteries.
[0018] (3) The preparation method of the present invention is to prepare the hydrotalcite aramid membrane composite material in one step by using the in-situ growth technology. The content ratio of the bimetallic and the immersion time and immersion temperature are reasonably controlled to realize the use of the aramid membrane as the carrier and anchor point of the hydrotalcite aramid membrane composite material, and finally obtain the hydrotalcite aramid membrane composite material, and then remove the excess ions by water washing to obtain a pure product. The preparation process is simple and the operability is strong.
[0019] (4) In the preparation process of the hydrotalcite aramid membrane composite material of the present invention, the role of the aramid membrane as a carrier and anchoring point of the hydrotalcite aramid membrane composite material is fully utilized. On the one hand, during the in-situ growth process, the membrane provides a position for ion anchoring as the fiber body, and maintains the uniform distribution and consistency of the structure during the growth of hydrotalcite in the solution. On the other hand, the aramid membrane is insoluble in water, and no additional cleaning agent needs to be added in the subsequent cleaning process. A pure product can be obtained by cleaning with green and environmentally friendly water.
[0020] (5) The method for preparing the hydrotalcite aramid diaphragm composite material of the present invention is simple and reliable to operate, has good repeatability, is environmentally friendly, and has low cost, and has broad prospects for industrial application of batteries. The hydrotalcite aramid diaphragm composite material of the present invention is particularly suitable for use as a lithium-ion battery diaphragm material, and the prepared lithium-ion battery has a good cycle life, high safety performance, and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the hydrotalcite aramid diaphragm composite material prepared in Example 2. DETAILED DESCRIPTION
[0022] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0024] A method for preparing a hydrotalcite-aramid membrane composite material comprises the following steps: adding a metal compound for preparing hydrotalcite and an aramid membrane into water, controlling the immersion temperature and immersion time, and after the hydrotalcite is in-situ grown on the aramid membrane, washing with clean water and drying to obtain the hydrotalcite-aramid membrane composite material, wherein the drying temperature is 70°C.
[0025] Specifically, the hydrotalcite is a double metal layered hydroxide or a single metal layered hydroxide; the size of the hydrotalcite is 100-1000 nm.
[0026] Preferably, the hydrotalcite is a bimetallic layered hydroxide.
[0027] Specifically, the hydrotalcite is at least one of nickel-containing cobalt oxide, nickel-containing aluminum oxide, nickel-containing magnesium oxide, nickel-containing iron oxide, iron-containing nickel oxide, iron-containing cobalt oxide, iron-containing calcium oxide, iron-containing magnesium oxide, iron-containing aluminum oxide, iron-containing sodium oxide, cobalt-containing nickel oxide, cobalt-containing iron oxide, cobalt-containing aluminum oxide, cobalt-containing magnesium oxide, cobalt-containing zirconium oxide, and cobalt-containing sodium oxide.
[0028] More specifically, the hydrotalcite is at least one of magnesium-aluminum hydrotalcite, nickel-cobalt hydrotalcite, calcium-magnesium hydrotalcite, cobalt-cobalt hydrotalcite, nickel-aluminum hydrotalcite, calcium-aluminum hydrotalcite, nickel-nickel hydrotalcite, cobalt-aluminum hydrotalcite, nickel-iron hydrotalcite, cobalt-iron hydrotalcite, magnesium-iron hydrotalcite, and iron-iron hydrotalcite.
[0029] Preferably, the hydrotalcite is nickel-cobalt hydrotalcite.
[0030] Specifically, the metal compound for preparing the hydrotalcite is selected from at least one of a first metal compound and a second metal compound; The first metal compound is selected from at least one of cobalt-containing oxides, cobalt-containing sulfides, cobalt-containing chlorides, cobalt-containing sulfates, cobalt-containing nitrates, cobalt-containing carbonates, magnesium oxides, magnesium-containing sulfides, magnesium-containing chlorides, magnesium-containing sulfates, magnesium-containing nitrates, and magnesium-containing carbonates; The second metal compound is selected from at least one of nickel-containing oxides, nickel-containing sulfides, nickel-containing chlorides, nickel-containing sulfates, nickel-containing nitrates, nickel-containing carbonates, aluminum-containing oxides, aluminum-containing chlorides, aluminum-containing sulfides, aluminum-containing hydroxides, aluminum-containing sulfates, aluminum-containing nitrates, and aluminum-containing carbonates.
[0031] Preferably, the metal compound used to prepare the hydrotalcite is a first metal compound and a second metal compound, and the mass ratio of the first metal compound to the second metal compound is 1:(2-6).
[0032] More preferably, the metal compounds used to prepare the hydrotalcite are nickel chloride and cobalt chloride.
[0033] Specifically, for each 30*30cm aramid diaphragm, the added amount of the metal compound is 2-6g; the mass ratio of the metal compound to water is 1:(75-200).
[0034] Specifically, in the preparation method, alkali is added to the water, and the alkali is at least one of sodium hydroxide and calcium oxide; the mass ratio of the metal compound to the alkali is 1: (0.5-6).
[0035] Specifically, the soaking temperature is 20-80° C., and the soaking time is 20 s-1 h.
[0036] More specifically, the soaking temperature is T , in ℃; the immersion time is Y, in s; then Y=y±8, y=-2585ln( T )+11341. And, the amount of the base added is a multiple of the mass of the metal oxide C (That is, the mass ratio of the metal compound to the base is 1: C );but C ≤(-0.05 Y +7). The relationship between the soaking temperature and soaking time, and the soaking temperature and the amount of alkali according to the above formula is more conducive to efficiently obtaining a hydrotalcite aramid diaphragm composite material with excellent performance.
[0037] Specifically, the aramid membrane is any one of a meta-aramid membrane, a para-aramid membrane, a bio-based aramid membrane, a meta-aramid ceramic membrane, a para-aramid ceramic membrane, a bio-based aramid ceramic membrane, a meta-aramid fiber membrane, a para-aramid fiber membrane, and a polyacrylonitrile membrane.
[0038] More specifically, the aramid membrane used in the embodiments of the present invention is a meta-aramid membrane (specific model: Yantai Taihe New Material Battery New Material Technology Co., Ltd. THM0722).
[0039] A hydrotalcite aramid diaphragm composite material is prepared according to the preparation method of the present invention.
[0040] An application of a hydrotalcite aramid diaphragm composite material, wherein the hydrotalcite aramid diaphragm composite material is applied as a lithium ion battery diaphragm material.
[0041] Example 1 Preparation of a hydrotalcite aramid diaphragm composite material: 1 g of cobalt chloride and 3 g of nickel chloride were added to 300 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 980 s at 55° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0042] Example 2 Preparation of a hydrotalcite aramid diaphragm composite material: Add 1g of cobalt chloride, 3g of nickel chloride and 2g of calcium oxide to 300g of water, stir evenly, add a 30*30cm aramid diaphragm, soak at 55°C for 980s, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0043] Example 3 Preparation of a hydrotalcite aramid diaphragm composite material: Add 1g of cobalt oxide, 2g of aluminum hydroxide and 8g of sodium hydroxide to 300g of water, stir evenly, add a 30*30cm aramid diaphragm, soak at 80°C for 20s, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0044] Example 4 Preparation of a hydrotalcite aramid diaphragm composite material: Add 1g of cobalt oxide, 2g of aluminum hydroxide, and 6g of calcium oxide to 300g of water, stir evenly, add a 30*30cm aramid diaphragm, soak at 80°C for 20s, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0045] Example 5 Preparation of a hydrotalcite aramid diaphragm composite material: 0.5 g of magnesium oxide and 3 g of aluminum chloride were added to 700 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 1 h at 20° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0046] Example 6 Preparation of a hydrotalcite aramid diaphragm composite material: Add 0.5 g of magnesium oxide, 3 g of aluminum chloride, and 21 g of calcium oxide to 700 g of water, stir evenly, add a 30*30 cm aramid diaphragm, soak at 20°C for 1 hour, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0047] Example 7 Preparation of a hydrotalcite aramid diaphragm composite material: 2 g of magnesium oxide and 4 g of aluminum chloride were added to 600 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 0.5 h at 40° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0048] Example 8 Preparation of a hydrotalcite aramid diaphragm composite material: Add 1 g of nickel sulfate and 3 g of aluminum sulfate to 400 g of water, stir evenly, add a 30*30 cm aramid diaphragm, soak at 40° C. for 0.5 h, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0049] Example 9 Preparation of a hydrotalcite aramid diaphragm composite material: 1 g of nickel carbonate and 2 g of magnesium carbonate were added to 300 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 750 s at 60° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0050] Example 10 Preparation of a hydrotalcite aramid diaphragm composite material: Add 1 g of cobalt chloride and 3 g of nickel chloride to 300 g of water, stir evenly, add a 30*30 cm aramid diaphragm, soak at 55° C. for 1 h, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0051] Embodiment 11 Preparation of a hydrotalcite aramid diaphragm composite material: Add 1g of cobalt chloride, 3g of nickel chloride and 20g of calcium oxide to 300g of water, stir evenly, add a 30*30cm aramid diaphragm, soak at 55°C for 980s, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0052] Example 12 Preparation of a hydrotalcite aramid diaphragm composite material: 4 g of cobalt chloride was added to 300 g of water, and after being stirred evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 980 s at 55° C., and then rinsed with clean water and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0053] Comparative Example 1 Synthesis of NiCo-LDH nanosheets: 1 g nickel nitrate, 3 g cobalt nitrate and 6 g sodium hydroxide were added to 1 L water, stirred evenly, heated to 70°C, maintained for 1 h, washed, and dried at 70°C for 1 h to obtain NiCo-LDH nanosheets.
[0054] The synthesized NiCo-LDH nanosheets were mixed into 1L of water, evenly coated on the surface of the aramid diaphragm, left to stand for 1 hour and then dried to obtain the product.
[0055] Comparative Example 2 The hydrotalcite aramid diaphragm composite material was prepared by the same method as in Example 1, except that the amount of the metal compound added was increased. In this comparative example 2, the amount of the metal compound added was 8 g (higher than the amount specified in the present invention). The specific preparation process was as follows: 2 g of cobalt chloride and 6 g of nickel chloride were added to 300 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 980 s at 55° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0056] Comparative Example 3 The hydrotalcite aramid diaphragm composite material was prepared by the same method as in Example 4, except that the amount of alkali added was increased. In this comparative example 3, the mass ratio of the metal compound to the alkali was 1:15 (higher than the amount specified in the present invention). The specific preparation process was as follows: Add 1 g of cobalt hydroxide, 2 g of aluminum hydroxide, and 45 g of sodium hydroxide to 300 g of water, stir evenly, add a 30*30 cm aramid diaphragm, soak at 80°C for 20 seconds, then rinse with clean water and dry to obtain a hydrotalcite aramid diaphragm composite material.
[0057] Comparative Example 4 The hydrotalcite aramid diaphragm composite material was prepared by the same method as in Example 1, except that the immersion temperature was increased. In this comparative example 4, the immersion temperature was 90° C. The specific preparation process was as follows: 1 g of cobalt chloride and 3 g of nickel chloride were added to 300 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 980 s at 90° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0058] Comparative Example 5 The hydrotalcite aramid diaphragm composite material was prepared by the same method as in Example 1, except that the immersion temperature was lowered. In this comparative example 4, the immersion temperature was 10° C. The specific preparation process was as follows: 1 g of cobalt chloride and 3 g of nickel chloride were added to 300 g of water, and after stirring evenly, a 30*30 cm aramid diaphragm was added, and the mixture was allowed to stand and soak for 980 s at 10° C., then rinsed with clean water, and dried to obtain a hydrotalcite aramid diaphragm composite material.
[0059] The diaphragm composite materials prepared in the above examples and comparative examples were subjected to heat resistance tests, wherein the test method involved is: Thickness test: GB / T 6672-2001 "Mechanical measurement method for thickness of plastic film and sheet"; Film rupture temperature: GB / T 36800.1-2018 "Thermomechanical analysis of plastics (TMA) Part 1: General principles"; Thermal shrinkage: Test according to GB / T 36363-2018. Draw a 10.0 cm × 10.0 cm line on the diaphragm along the MD × TD direction. Sandwich the diaphragm between two A4 papers and put it in an oven. Measure three samples at the same temperature and take the average value as the test result.
[0060] The specific test results are shown in Table 1.
[0061] Table 1 Test results of thickness and heat resistance of diaphragm composite materials
[0062] Note: MD in Table 1 stands for longitudinal direction and TD stands for transverse direction.
[0063] In addition, a method for preparing a lithium-ion battery and testing its performance using a hydrotalcite aramid diaphragm composite material is as follows: the diaphragm composite material prepared in the above embodiments and comparative examples is punched out into a diaphragm of standard size using a standard punching machine, and a 2032 button cell is assembled using a metal lithium sheet and graphite as a comparative electrode, the electrolyte used is 1.0 M LiPF6 / EC / DEC, and the charge and discharge current density used to test the cycle performance is 1C. The specific test results are shown in Table 2 below.
[0064] Table 2 Battery performance test results
[0065] Figure 1 This is a scanning electron microscope image (SEM) of the hydrotalcite aramid diaphragm composite material prepared in Example 2. Figure 1It can be seen that the hydrotalcite nanosheets grow evenly on each fiber of the aramid diaphragm, and the size of each hydrotalcite nanosheet is at the nanometer level, so the thickness of the diaphragm itself will not be increased. Secondly, since the hydrotalcite grows in situ on each fiber, the heat resistance of the hydrotalcite is perfectly combined with the aramid diaphragm, which can greatly improve the heat resistance of the diaphragm. Finally, the hydrotalcite grows in situ on the fibers of the aramid diaphragm, and will not produce agglomeration and accumulation, and will not produce powder loss under physical mixing, and will not pollute the battery assembly line, which greatly improves the assembly efficiency.
[0066] It can be seen from the data in Table 1 and Table 2 above that: Example 1-Example 12 The hydrotalcite aramid membrane composite material prepared by the preparation method of the present invention is based on the aramid membrane, and utilizes the in-situ growth method of the hydrotalcite nanomaterial to evenly distribute the hydrotalcite nanosheets which have heat-resistant properties on each fiber of the aramid membrane, so as to give full play to the heat-resistant properties of aramid and hydrotalcite. At the same time, the numerous active hydroxyl groups and interlayer anions on the surface of the hydrotalcite motherboard provide a lot of adsorption sites, which accelerates the transmission speed of lithium ions, broadens the transmission path of lithium ions, and further improves the ionic conductivity of the membrane. Applying it to lithium-ion batteries can improve the cycle stability and safety performance of lithium batteries.
[0067] From the data comparison of Example 1, Example 5 with Example 2, Example 3, Example 4, and Example 6, it can be seen that during the preparation process of Example 2, Example 3, Example 4, and Example 6, the addition of an appropriate amount of alkali can make the hydrotalcite adhere more evenly to the aramid diaphragm, and the final hydrotalcite aramid diaphragm composite material has better heat resistance and better application effect in lithium-ion batteries.
[0068] From the data comparison between Example 1 and Example 10, it can be seen that when the immersion temperature and immersion time satisfy Y=y±8, y=-2585ln( T )+11341, which is more conducive to efficiently obtaining a hydrotalcite aramid diaphragm composite material with excellent performance. From the comparison of the data of Example 2 and Example 11, it can be seen that the soaking temperature and the amount of alkali are in accordance with C ≤(-0.05 Y +7), it is more conducive to efficiently obtaining a hydrotalcite aramid diaphragm composite material with excellent performance. Because the immersion temperature, immersion time and alkali dosage cooperate with each other, the in-situ growth rate and growth state of hydrotalcite can be controlled, which is more conducive to the uniform distribution of hydrotalcite on the aramid diaphragm, and ultimately improves the heat resistance and battery application performance of the hydrotalcite aramid diaphragm composite material.
[0069] From the data comparison of Example 1 and Example 12, it can be seen that the bimetallic layered hydroxide on the aramid membrane of Example 1 is more conducive to improving the heat resistance and battery application performance of the aramid membrane composite material than the single metal layered hydroxide in Example 12.
[0070] From the data comparison of Example 1 and Comparative Example 1, it can be seen that the preparation method of the present invention introduces hydrotalcite in situ growth on the aramid membrane, which is more conducive to the uniform distribution and consistency of hydrotalcite compared with the coating method of Comparative Example 1, and ultimately improves the application performance of the hydrotalcite aramid membrane composite material.
[0071] From the data comparison of Example 1 and Comparative Example 2, it can be seen that if the amount of metal compound added is too much, the heat resistance of the hydrotalcite aramid membrane composite material will decrease, because the excessive amount of metal compound will affect the uniformity of the distribution of hydrotalcite on the aramid membrane, and the problem of hydrotalcite accumulation will easily occur on the aramid membrane, which will eventually lead to a decrease in the performance of the hydrotalcite aramid membrane composite material.
[0072] From the experimental comparison of Example 4 and Comparative Example 3, it can be seen that excessive addition of alkali will also lead to poor performance of the aramid diaphragm composite material, because too strong alkalinity will accelerate the growth rate of hydrotalcite nanosheets, resulting in too short a nucleation time of hydrotalcite nanosheets, agglomeration and accumulation, causing hydrotalcite to fall off and ion conductivity to decrease. In addition, too strong alkalinity will corrode the diaphragm and cause it to break.
[0073] From the comparison of the data of Example 1 and Comparative Example 4, it can be seen that if the immersion temperature is too high, the heat resistance of the hydrotalcite aramid diaphragm composite material decreases, because the temperature is too high, the growth rate of the hydrotalcite is too fast, and it is easy to be unevenly distributed on the aramid diaphragm.
[0074] From the comparison of the data of Example 1 and Comparative Example 5, it can be seen that if the immersion temperature is too low, sufficient hydrotalcite cannot be formed in situ on the aramid membrane, and the aramid membrane composite material cannot meet the requirements of good heat resistance. Therefore, the temperature conditions defined in the present invention are more conducive to obtaining a hydrotalcite aramid membrane composite material with excellent performance.
[0075] In summary, the hydrotalcite aramid diaphragm composite material of the present invention has nano-scale hydrotalcite nanosheets with a large specific surface area. At the same time, a large number of active hydroxyl groups and interlayer anions on the surface of the hydrotalcite can provide a large number of lithium ion adsorption sites, which is conducive to improving the ion transmission rate, broadening the ion transmission path, and providing a basis for high-rate charge and discharge. The hydrotalcite grows in situ in the aramid diaphragm fiber without increasing the thickness of the diaphragm, improving the high-temperature heat shrinkage performance of the diaphragm, and improving the energy density, long cycle performance and high-rate discharge capability of the battery cell.
[0076] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0077] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing a hydrotalcite aramid diaphragm composite material, characterized in that: The preparation method comprises the following steps: adding a metal compound for preparing hydrotalcite and an aramid membrane into water, controlling the soaking temperature and soaking time, and after the hydrotalcite grows in situ on the aramid membrane, washing with clean water and drying the hydrotalcite aramid membrane composite material.
2. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 1, characterized in that: The hydrotalcite is a double metal layered hydroxide or a single metal layered hydroxide; the size of the hydrotalcite is 100-1000 nm.
3. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 1, characterized in that: The hydrotalcite is at least one of nickel-containing cobalt oxide, nickel-containing aluminum oxide, nickel-containing magnesium oxide, nickel-containing iron oxide, iron-containing nickel oxide, iron-containing cobalt oxide, iron-containing calcium oxide, iron-containing magnesium oxide, iron-containing aluminum oxide, iron-containing sodium oxide, cobalt-containing nickel oxide, cobalt-containing iron oxide, cobalt-containing aluminum oxide, cobalt-containing magnesium oxide, cobalt-containing zirconium oxide, and cobalt-containing sodium oxide.
4. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 1, characterized in that: The metal compound for preparing the hydrotalcite is selected from at least one of a first metal compound and a second metal compound; The first metal compound is selected from at least one of cobalt-containing oxides, cobalt-containing sulfides, cobalt-containing chlorides, cobalt-containing sulfates, cobalt-containing nitrates, cobalt-containing carbonates, magnesium oxides, magnesium-containing sulfides, magnesium-containing chlorides, magnesium-containing sulfates, magnesium-containing nitrates, and magnesium-containing carbonates; The second metal compound is selected from at least one of nickel-containing oxides, nickel-containing sulfides, nickel-containing chlorides, nickel-containing sulfates, nickel-containing nitrates, nickel-containing carbonates, aluminum-containing oxides, aluminum-containing chlorides, aluminum-containing sulfides, aluminum-containing hydroxides, aluminum-containing sulfates, aluminum-containing nitrates, and aluminum-containing carbonates.
5. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 4, characterized in that: The metal compound used to prepare the hydrotalcite is a first metal compound and a second metal compound, and the mass ratio of the first metal compound to the second metal compound is 1:(2-6).
6. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 1, characterized in that: For each 30*30cm aramid diaphragm, the added amount of the metal compound is 2-6g; the mass ratio of the metal compound to water is 1:(75-200).
7. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 1, characterized in that: In the preparation method, a base is added to the water, and the base is at least one of sodium hydroxide or calcium oxide; The mass ratio of the metal compound to the base is 1:(0.5-6).
8. The method for preparing a hydrotalcite aramid diaphragm composite material according to claim 1, characterized in that: The soaking temperature is 20-80° C., and the soaking time is 20 s-1 h.
9. A hydrotalcite aramid diaphragm composite material, characterized in that: The hydrotalcite aramid diaphragm composite material is prepared according to the preparation method according to any one of claims 1-8.
10. An application of the hydrotalcite aramid diaphragm composite material according to claim 9, characterized in that: The hydrotalcite aramid diaphragm composite material is used as a lithium ion battery diaphragm material.
Citation Information
Patent Citations
Preparation method of organic intercalation hydrotalcite-aramid fiber coating liquid and application of organic intercalation hydrotalcite-aramid fiber coating liquid in lithium battery diaphragm coating
CN114479654A
Lithium ion battery composite diaphragm and preparation method thereof
CN114243217A
Ceramic diaphragm as well as preparation method and application thereof
CN115911755A
Rechargeable lithium battery
KR1020110058129A
Separator having aramid fibrous layer with high strength and secondary battery having the same
KR1020130085139A
Cited By
Magnetic field regulation and control magnesium-iron double-metal hydroxide ordered alkaline diaphragm and preparation method thereof
CN121628179A
